Embodied Organizational Routines: Explicating a Practice Understanding. (April 2019) - Wright, Alex
This article contributes to theory development through advancing an embodied framing of organizational routines. It addresses the absence of bodies in a literature that tends to treat the "people" involved in organizational routines as disembodied actors. One consequence of this is that progress toward a theory of "routines as practices" has tended to ignore how bodies contribute to their unfolding. Theorizing embodied communicative acts brings the body and embodiment into organizational routines research. Existing knowledge is extended by drawing from multiple empirical illustrations to explain how routines are accomplished when power is exercised through gesture and bodily movement, the spaces where routines unfold cohere with human bodies making a difference in how they are constituted and experienced, and, the routineness of routines is made manifest when mutual intelligibility is discerned in the silences that characterize how embodied actors interrelate.